The Trivial Horizons of the Ethics of Interpretation of Vattimo. - Domeracki, Piotr (Filozofia Chrześcijańska, 2009)
Vattimo is an author of so-called radicalized hermeneutics. In it he refers creatively to the counter-metaphysical nihilism of Nietzsche and Heidegger. He is accompanied by an intention of radicalization (weakening) both these positions with hope for clearing them of the remains of metaphysical thinking. The nihilistic accomplishment of hermeneutics Vattimo combines with its transition to the ethical position. However he polemizes with approaches, which develop “an ethical vocation” of hermeneutics either in the direction of the ethics of communication (like Habermas), or in the direction of the ethics of redescription (like Rorty), or in the direction of the ethics of continuation (like Gadamer). In their place Vattimo suggests the ethics of interpretation, which is rather ethics of goods than ethics of obligations. It is a kind of a retrospective (historical), pluralistic, relativistic ethics with a preference for the value of freedom.